The Association Between Habitual Sleep Duration and Mortality According to Sex and Age: The Japan Public Health Center-based Prospective Study - Thomas Svensson; Manami Inoue; Eiko Saito; Norie Sawada; Hiroyasu Iso; Tetsuya Mizoue; Atsushi Goto; Taiki Yamaji; Taichi Shimazu; Motoki Iwasaki; Shoichiro Tsugane (Journal of Epidemiology, 2021)
Background: Short and long sleep durations are associated with mortality outcomes. The association between sleep duration and mortality outcomes may differ according to sex and age. Methods: Participants of the Japan Public Health Center-based prospective study (JPHC Study) were aged 40–69 years and had completed a detailed questionnaire on lifestyle factors. Sex- and age-stratified analyses on the association between habitual sleep duration and mortality from all-causes, cardiovascular diseases (CVD), cancer and other causes included 46,152 men and 53,708 women without a history of CVD or cancer. Cox proportional hazards regression models, adjusted for potential confounders, were used to determine hazard ratios and 95% confidence intervals. Results: Mean follow-up time was 19.9 years for men and 21.0 years for women. In the multivariable sex-stratified models, some categories of sleep durations ≥8 hours were positively associated with mortality from all-causes, CVD, and other causes in men and women compared with 7 hours. The sex- and age-stratified analyses did not reveal any major differences in the association between sleep duration and mortality outcomes in groups younger and older than 50 years of age. The only exception was the significant interaction between sleep duration and age in women for mortality from other causes. Conclusions: Sleep durations ≥8 hours are associated with mortality outcomes in men and women. Age may be an effect modifier for the association between sleep duration and mortality from other causes in women.